Description of a new Chaetopelma (Araneae, Theraphosidae) species from Crete and a re-description of Macrothele cretica Kulczyński, 1903 (Araneae, Macrothelidae) - Chatzaki, Maria; Komnenov, Marjan (Zootaxa, 2019)
The family Theraphosidae is recorded from Greece for the first time with the description of a new species, Chaetopelma lymberakisi sp. n. Also, the male of Macrothele cretica Kulczyński, 1903 is re-described and the female of the same species is described for the first time.